International survey on high‐ and low‐dose synacthen test and assessment of accuracy in preparing low‐dose synacthen. (22nd February 2018) - Cross, Alexandra S.; Helen Kemp, E.; White, Anne; Walker, Leanne; Meredith, Suzanne; Sachdev, Pooja; Krone, Nils P.; Ross, Richard J.; Wright, Neil P.; Elder, Charlotte J.
Summary: Objective: The short synacthen test (SST) is widely used to assess patients for adrenal insufficiency, but the frequency and protocols used across different centres for the low‐dose test (LDT) are unknown. This study aimed to survey centres and test the accuracy of ten different synacthen preparation strategies used for the LDT. Methods: Members of 6 international endocrine societies were surveyed regarding diagnostic tests used for adrenal insufficiency, and in particular the SST. Synacthen was diluted for the LDT and concentrations measured using a synacthen ELISA. Results: Survey responses were received from 766 individuals across 60 countries (52% adult, 45% paediatric endocrinologists). The SST is used by 98% of centres: 92% using high‐dose (250 μg), 43% low‐dose and 37% both. Ten low‐dose dilution methods were assessed and variation in synacthen concentration was demonstrated with intramethod coefficients of variation (CV) ranging from 2.1% to 109%. The method using 5% dextrose as a diluent was the least variable (CV of 2.1%). The variation in dilution methods means that the dose of synacthen administered in a LDT may vary between 0.16 and 0.81 μg. Conclusions: The high‐dose SST is the most popular diagnostic test of adrenal insufficiency, but up to 72% of paediatric endocrinologists use a LDT. There is considerable variation observed both within and between low‐dose synacthen dilution methods creating considerable risk of inaccurate dosing and thereby invalid results.